The role of non-canonical SNAREs in synaptic vesicle recycling - Ramirez, Denise M.O. (Landes Bioscience, 2012)
An increasing number of studies suggest that distinct pools of synaptic vesicles drive specific forms of neurotransmission. Interspersed with these functional studies are analyses of the synaptic vesicle proteome which have consistently detected the presence of so-called “non-canonical” SNAREs that typically function in fusion and trafficking of other subcellular structures within the neuron. The recent identification of certain non-canonical vesicular SNAREs driving spontaneous (e.g., VAMP7 and vti1a) or evoked asynchronous (e.g., VAMP4) release integrates and corroborates existing data from functional and proteomic studies and implies that at least some complement of non-canonical SNAREs resident on synaptic vesicles function in neurotransmission. Here, we discuss the specific roles in neurotransmission of proteins homologous to each member of the classical neuronal SNARE complex consisting of synaptobrevin2, syntaxin-1 and SNAP-25.